Genetic resistance to gastrointestinal parasites in sheep - Poli, Mario Andres (2023)
Gastrointestinal nematode (GIN) infection is the most common disease affecting sheep production systems throughout the world, causing significant productive and economic losses. The control of these parasites was traditionally based on the use of anthelmintic drugs. However, continuous, extensive, and indiscriminate use of these drugs has led to the emergence and spread of strains of parasites resistant to the major chemical compounds used. This situation has led to considering alternative strategies for worm control. One of them is the selection of individuals for greater resistance to GINs. A number of phenotypic traits have been reported in the bibliography, including parasitological, biochemical, hematological, and immunological traits, but fecal egg count (FEC) is considered the primary and most practical measure of resistance. Genomic studies have reported polymorphisms associated with GIN resistance traits on almost all sheep chromosomes. Among other loci, FEC has been associated with the major histocompatibility complex (MHC) through quantitative trait loci (QTL) analysis and genome-wide association studies (GWAS). This review covers the principal aspects reported in the literature on several parameters considered to evaluate the resistance status of sheep to nematodes, mainly Haemonchus contortus, the correlation between resistance markers with economically important production traits, and the main genomic regions identified as relevant in determining the phenotype for resistance or susceptibility to GINs.